Assessment of the Relationship Between Orthorexia Nervosa, Eating Attitudes and Behaviors, and Obsessive-Compulsive Disorder in University Students - Gomleksiz, Mehtap; Yarasir, Ezgi (Wiley, 2025)
Background: This study aimed to determine the psychosocial risk factors for orthorexia nervosa (ON) in university students and to evaluate the relationship between eating attitudes and behaviors and obsessive-compulsive disorder (OCD). Methods: A cross-sectional study was conducted with 882 university students in an eastern Turkish province from October to December 2023. Data for the study were collected using a sociodemographic survey form, the Orthorexia Nervosa Test (ORTO-15), the Eating Attitude Test (EAT-40), and the Obsessive-Compulsive Inventory-Revised (OCI-R) assessments. Additionally, an online survey was administered to the participants using Google Forms. The collected data were analyzed using the SPSS 22.0 statistical software program. Results: The participants had a mean age of 20.9 +/- 3.0 years (range: 17-45), and 73.1% (n = 645) were female. Orthorexic tendencies were observed in 14.7% of the participants, impaired eating behavior in 15.6%, and a risk of OCD in 58.7%. The mean ORTO-15 score for the participants was 37.3 +/- 3.6, the mean EAT-40 score was 20.0 +/- 15.5, and the mean OCI-R score was 25.9 +/- 15.0. ORTO-15 scores were significantly higher among participants in their sixth year of study and those enrolled in evening education programs (p < 0.05). EAT-40 scores were significantly higher in students aged 20-22, those with poor socioeconomic status, and smokers (p < 0.05). OCI-R scores were notably higher in participants who lived in dormitories during their studies and those who had quit smoking (p < 0.05). While ORTO-15 scores were negatively correlated with EAT-40 scores (p < 0.05), a weak positive correlation was observed between OCI-R and EAT-40 scores (p < 0.05). Conclusion: Although ON, OCD, and eating disorders seem to be different disorders, they both have similar characteristics. Further studies are needed to investigate possible risk factors of comorbidity.
Keywords: eating behavior; eating disorder; obsessive-compulsive disorder; orthorexia nervosa